ANALISIS STRATEGI PENGELOLAAN MANGROVE MENGGUNAKAN METODE PERBANDINGAN EKSPONENSIAL DI KOTA SORONG PAPUA BARAT - Yetty S. Serkadifa; John M. Matinahoru; D. V. Pattimahu (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2018)
The Benefits of mangrove ecosystems are varied, it can be seen from the ecological aspect, economic , social and protection functions. Mangrove forests can be found along the coastal area of Sorong city, the density of the mangrove forests forest are variaed with the total mangrove area on site research 101 ha, current conditions shows that it is necessarily need a strategy in management mangrove, with the aim of priority strategies can analyze mangrove management. Then in the analysis using the method of comparison of the exponential (MPE), menjukan that the research results from the analysis of the stretegi mangrove management developments, of the factors that influence that is a major ecological 45.54%, and of the actor who portrays in the management of mangrove forests that is the Government amounting to 50.89%. So the priority strategy in the management of controlling management plan and a plan of action in the management of mangroves of 32.84%..